Hadamard Inequalities for Strongly α,m-Convex Functions via Caputo Fractional Derivatives - Yanliang Dong; Muhammad Zeb; Ghulam Farid; Sidra Bibi (Journal of Mathematics)
In this paper, we present two versions of the Hadamard inequality for α,m convex functions via Caputo fractional derivatives. Several related results are analyzed for convex and m-convex functions along with their refinements and generalizations. The error bounds of the Hadamard inequalities are established by applying some known identities.